2018
DOI: 10.4066/biomedicalresearch.29-18-270
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence factors, phylogroups, serogroups and biofilm formation among CTX-M-1 positive Escherichia coli isolated from patients with pyelonephritis

Abstract: Objectives: Urinary tract infections are among the most frequent infections caused by Escherichia coli isolates. The aims of this study were determination of antibiotic susceptibility and detection of virulence genes, phylogroups, serogroups and biofilm formation of E. coli isolates from patients with pyelonephritis. Methods: A total of 20 E. coli isolates were isolated from pyelonephritis. The antimicrobial susceptibility test was performed for eleven antibiotic disks. The biofilm formation assay was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The significant negative association with diarrhea for the yjaA gene reported in the study of Afset et al (6) and suggested that the presence of the yjaA gene may be a marker for low diarrheagenic potential aEPEC strains. The yjaA gene as the negative marker for diarrhea may be one possible reason for the association of B2 phylogenetic group with extraintestinal E. coli infections (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The significant negative association with diarrhea for the yjaA gene reported in the study of Afset et al (6) and suggested that the presence of the yjaA gene may be a marker for low diarrheagenic potential aEPEC strains. The yjaA gene as the negative marker for diarrhea may be one possible reason for the association of B2 phylogenetic group with extraintestinal E. coli infections (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%